A gestão socioambiental do risco e o papel do direito no tratamento dos desastres antropogênicos com rompimentos de barragens de rejeitos no Brasil - Bacchi, Kethelen Severo (2024)
The current portrait of Brazil, in the activity with mining dams, has been highlighted by a history of failures in these structures, involving fatalities and environmental damage, which generates social unrest. This situation demonstrates that the constitutional guidance for the prevention and control of risks arising from economic activities has not been observed. Therefore, it is worth asking to what extent the Law, through the Theory of Disaster Law, and especially socio-environmental risk management, is applied in the treatment of anthropogenic disasters? Therefore, the general objective of the study is to investigate how Law, in the socio-environmental management of risk, can be applied in the treatment of anthropogenic disasters in Brazil, especially in the case of tailings dam collapses. The work is based on predominantly bibliographical research, with documentary support, as existing documents on the topic will be considered. The approach method will be deductive and the research procedure methods wil l be the monographic or case study method and the comparative method. First, a historical analysis of anthropogenic disasters and vulnerabilities will be presented. Secondly, details will be provided on the Law of Disasters and its implications, and, finally, the socio-environmental risk management applied to tailings dam failures in Brazil will be presented. Thus, the latent fragility of the Brazilian legal system in the face of disasters was concluded, and in this case, mainly those related to tailings dam collapses. Within this panorama, law emerges as a tool capable of bringing stability, guaranteeing justice in the midst of collapse. Added to this is the use of circular socio-environmental risk management as a method, within the Disaster Law Theory, to be implemented with the aim of reducing the occurrence of tailings dam failures, especially in the prevention and mitigation phases.